Emergent sampling of Bryozoa in Mackellar glaciomarine fjord, 62°S maritime Antarctic - Mariana Pita; Aldo Gonzalo Indacochea; Bernabé Moreno (Ukrainian Antarctic Journal, 2025)
Bryozoans are sessile suspension feeding metazoans which represent an important component of Antarctic macrozoobenthic communities. These ectotherm modular organisms are present in a wide variety of habitats subjected to strong gradients, such as those found in polar glaciomarine fjords. This study focused on the diversity of bryozoans opportunistically collected via van Veen grab deployments during four summer campaigns (2017–2019 and 2023) in Mackellar Inlet (62. S, King George Island) by Peruvian ANTAR expeditions. The cumulative taxa richness and diversity patterns were evaluated, revealing an overall number of 36 taxa, representing 84% of the estimated richness (Chao2 = 43). From the six recognised growth forms, the membraniporiforms (calcified encrusting unilaminar) dominated the bryozoan assemblage, followed by cheilostomes with flustriform growth habit. The highest diversity, cumulative taxonomic richness (26 taxa), and all growth forms herein recorded (6) were found in the outer section of the fjord. The erect flexible basibiont Nematoflustra flagellata (Waters, 1904) was the most abundant flustriform and hosted the highest abundance of epizoozoans, which preferred the rear surface of their host fronds for settlement. Unconsolidated deposits such as gravels and coarse sand grains were essential substrates for bryozoan assemblages; however, habitat-facilitating growth forms increased the overall values of abundance and taxonomic and functional richness at a local scale. This work, which is opportunistic in nature, represents a baseline for future studies aiming to create an annotated checklist of bryozoans in the area that would require diverse sampling methodologies focused specifically on bryozoans and their substrates (e.g., scuba diving, rock dredges). Although we aimed to cover a basic functional analysis based on growth forms, a deeper understanding of the ecology of bryozoans in Mackellar Inlet is needed, considering different ecological implications and life strategy adaptations to environmental gradients.